Pengaruh Model Example non Example dalam Pembelajaran Keterampilan Menulis Teks Deskripsi Siswa Kelas VII UPT SMP Negeri 1 Air Putih Kabupaten Batu Bara - Lidya Natalia Sibarani; Jumaria Sirait; Martua Reynhat Sitanggang Gusar (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2022)
This study aims to determine the effect of the example non example model in learning descriptive text writing skills for class VII students of UPT SMP Negeri 1 Air Putih, Batu Bara Regency. In this study using a quantitative method with the type of Pre-Experimental Design using a one-group pretest-posttest design. The sampling used in this research is purposive sampling technique. The data collection technique used is a descriptive text writing test. The results of the research on writing descriptive text before using the example non example model reached an average value of 50.78 in the less category. Meanwhile, the results of the study of writing descriptive text after using the example non example model reached an average value of 72.5 in the good category. Based on the results of the pre-test and post-test, there is an effect on the results of writing descriptive text with tcount 5.19. At a significant level of 0.05 (95% confidence level) with df = 31 obtained ttable = 1.69; significant at p < 0.05. Thus H0 is rejected. With the rejection of H0 then Ha is accepted, meaning that there is a significant influence on the writing skills of the seventh grade students of SMP Negeri 1 Air Putih, Batu Bara Regency using the non-example model.